Public Service Transformation: A Literature Review on the Role of Technology in Improving Service Quality - Gantika, Soma (Golden Ratio of Social Science and Education, 2025)
The application of technology in public services has become an essential topic in various discussions on service efficiency and quality. However, in Indonesia, the implementation of technology in the public sector still faces multiple challenges that need to be further analyzed. This research aims to explore the role of technology in improving the quality of public services in Indonesia, focusing on e-government, big data analytics, and artificial intelligence (AI), as well as the supporting factors that influence its success. The method used in this research is a literature review, which reviews various previous studies on the application of technology in the public sector in Indonesia and developed countries. Technologies such as e-government, big data analytics, and AI have been proven to improve the efficiency and transparency of public services in developed countries. However, in Indonesia, the implementation still faces obstacles, such as low digital literacy among employees and the public and resistance to change. Factors that support technology implementation include digital literacy, organizational readiness, and pro-digitalization government policies. The implementation of digital technology has great potential to improve the quality of public services in Indonesia. However, existing challenges must be overcome, especially regarding infrastructure, digital literacy, and supportive policies. Improving digital literacy and organizational readiness are key to successful digital transformation in the public sector.